2021
DOI: 10.3390/antibiotics10040444
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Staphylococcus aureus and Streptococcus pneumoniae Isolates from the Nasopharynx of Febrile Children under 5 Years in Nanoro, Burkina Faso

Abstract: (1) Background: nasopharynx colonization by resistant Staphylococcus aureus and Streptococcus pneumoniae can lead to serious diseases. Emerging resistance to antibiotics commonly used to treat infections due to these pathogens poses a serious threat to the health system. The present study aimed to determine the antibiotic susceptibility of S. aureus and S. pneumoniae isolates from the febrile children’s nasopharynx under 5 years in Nanoro (Burkina Faso). (2) Methods: bacterial isolates were identified from nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Regarding urine samples, the results of our study showed that the number of isolates of S. aureus bacteria reached 20 isolates, a rate of 65%. This result is contrary to the result of the researcher [10], who obtained a rate of 17% of S. aureus isolates from urine samples, and our results are consistent with The findings of the researcher [9], who obtained a high percentage of 86% of S. aureus bacteria isolates from urine samples. The reason for the difference in these percentages in each study mentioned above may be due to bias in collecting samples or to the nature of the size of the research sample included in the study, in addition to the health and immune status of the patients included in each study and the type of colonizing bacteria for each individual.…”
Section: Morphological Identificationsupporting
confidence: 63%
“…Regarding urine samples, the results of our study showed that the number of isolates of S. aureus bacteria reached 20 isolates, a rate of 65%. This result is contrary to the result of the researcher [10], who obtained a rate of 17% of S. aureus isolates from urine samples, and our results are consistent with The findings of the researcher [9], who obtained a high percentage of 86% of S. aureus bacteria isolates from urine samples. The reason for the difference in these percentages in each study mentioned above may be due to bias in collecting samples or to the nature of the size of the research sample included in the study, in addition to the health and immune status of the patients included in each study and the type of colonizing bacteria for each individual.…”
Section: Morphological Identificationsupporting
confidence: 63%
“…Streptococcus pneumoniae is a Gram-positive bacterium which is a particular challenge for neonates and the elderly adults. Previous studies have concentrated on the phenomena associated with colonization, carriage rate and transmission [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. However, the events occurring after S. pneumoniae breaks the first barriers of protection in the nasopharynx, the invasion of the host, are still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating antibiotic access and use outside facilities in LMICs concluded that long waiting times in healthcare facilities, easy and unrestricted accessibility of drug retail outlets in communities, and a lower cost per treatment course dispensed were the main reasons for accessing antibiotics without prior formal consultation [16][17][18]. While largely overlooked in antimicrobial stewardship, antimicrobial dispensing and use outside healthcare facilities may contribute towards maintaining a high AMR burden [19][20][21]. Studying the reasons underlying healthcare seeking outside healthcare facilities is crucial to develop contextspecific interventions and to inform policy change.…”
Section: Introductionmentioning
confidence: 99%